Multi-level biological responses in Ucides cordatus (Linnaeus, 1763) (Brachyura, Ucididae) as indicators of conservation status in mangrove areas from the western atlantic - Duarte, Luis Felipe de Almeida [UNESP]; Souza, Caroline Araújo de [UNESP]; Nobre, Caio Rodrigues; Pereira, Camilo Dias Seabra; Pinheiro, Marcelo Antonio Amaro [UNESP] (Elsevier, 2016)
There is a global lack of knowledge on tropical ecotoxicology, particularly in terms of mangrove areas. These areas often serve as nurseries or homes for several animal species, including Ucides cordatus (the uçá crab). This species is widely distributed, is part of the diet of human coastal communities, and is considered to be a sentinel species due to its sensitivity to toxic xenobiotics in natural environments. Sublethal damages to benthic populations reveal pre-pathological conditions, but discussions of the implications are scarce in the literature. In Brazil, the state of São Paulo offers an interesting scenario for ecotoxicology and population studies: it is easy to distinguish between mangroves that are well preserved and those which are significantly impacted by human activity. The objectives of this study were to provide the normal baseline values for the frequency of Micronucleated cells (MN‰) and for neutral red retention time (NRRT) in U. cordatus at pristine locations, as well to indicate the conservation status of different mangrove areas using a multi-level biological response approach in which these biomarkers and population indicators (condition factor and crab density) are applied in relation to environmental quality indicators (determined via information in the literature and solid waste volume). A mangrove area with no effects of impact (areas of reference or pristine areas) presented a mean value of MN‰<3 and NRRT>120 min, values which were assumed as baseline values representing genetic and physiological normality. A significant correlation was found between NRRT and MN, with both showing similar and effective results for distinguishing between different mangrove areas according to conservation status. Furthermore, crab density was lower in more impacted mangrove areas, a finding which also reflects the effects of sublethal damage; this finding was not determined by condition factor measurements. Multi-level biological responses were able to reflect the conservation status of the mangrove areas studied using information on guideline values of MN‰, NRRT, and density of the uçá crab in order to categorize three levels of human impacts in mangrove areas: PNI (probable null impact); PLI (probable low impact); and PHI (probable high impact). Results confirm the success of U. cordatus species’ multi-level biological responses in diagnosing threats to mangrove areas. Therefore, this species represents an effective tool in studies on mangrove conservation statuses in the Western Atlantic.
Keywords: Cytotoxicity; Density; Environmental safety; Genotoxicity; Mangrove; Ucides cordatus